An engraving by E. Therond, from a French magazine, 'Le Tour du Monde'... - E. Therond (Wikimedia Commons, 1874)
Notice iconographique issue de Wikimedia Commons. Titre: An engraving by E. Therond, from a French magazine, 'Le Tour du Monde', 1874 | *a very large scan of this engraving*. An engraving by E. Therond, from a French magazine, 'Le Tour du Monde', 1874 | *a very large scan of this engraving*
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie